THE EFFECT OF TRADITIONAL TAPE YEAST (Saccharomyces Cerevisiae) PERCENTAGE ON THE PHYSICAL AND CHEMICAL QUALITY OF VIRGIN COCONUT OIL (VCO) - Devina Arini; Devi Tanggasari (Universitas Muhammadiyah Mataram, 2025)
Coconut is a highly promising crop due to the wide variety of products that can be derived from it. One important form of coconut utilization is its processing into Virgin Coconut Oil (VCO). VCO can be produced through a fermentation method using yeast. This study aimed to evaluate the effect of different percentages of traditional ragi tape (Saccharomyces cerevisiae) on the physical and chemical quality of VCO. The experiment was conducted using a Completely Randomized Design with a single factor consisting of four treatments: 0%, 5%, 10%, and 15% ragi tape starter, each with three replications. Physical quality parameters included aroma, taste, and color, while chemical quality parameters comprised moisture content, free fatty acid (FFA) content, and peroxide value. The results showed that the percentage of ragi tape had no significant effect on the physical quality of VCO but significantly affected yield and chemical quality. The highest yield (23.3%) was obtained at the 15% treatment; however, the moisture content at 10% and 15% did not meet the SNI 7381:2022 standard. FFA levels in all treatments complied with the standard, whereas peroxide values in all treatments exceeded the SNI limit. Considering the balance between yield and chemical quality, the 5% ragi tape treatment was determined to be the best.